Assessing the Design of Websites for Governmental Departments Using HCI - Shahidzai, Amir Kuror (Journal of Natural Sciences – Kabul University, 2021)
Usability and Human-Computer Interaction (HCI) are key attributes of system development. Improving system facilities and ensuring that user needs and HCI requirements are met helps designers, analysts, and users better understand the system. This study assists designers in choosing appropriate text styles, fonts, layouts, graphics, and colors. Additionally, users will find the websites satisfying, safe, easy to learn, and visually appealing. Adopting these principles helps system developers achieve their goals, creating systems that users find relaxing and enjoyable to use. This study investigates several e-government websites and highlights their positive and negative aspects based on HCI principles.